Probabilistic analysis of the hull-girder still water loads on a shuttle tanker in full load condition, for parametrically distributed collision damage spaces. (December 2015) - Rodrigues, J.M.; Teixeira, A.P.; Guedes Soares, C.
Abstract: Box-shaped damage affected volumes are applied, with parametric variation of their positions and extensions, to an otherwise intact shuttle tanker in full load condition. The vessel's deadweight is numerically calculated and the lightweight is estimated using semi-empirical formulations to a great extent. For each damage configuration, the final position attained by the ship is investigated and the corresponding global loads are assessed, in terms of still water vertical bending moment and shear force. The ship is considered to be floating in the absence of waves and a quasi-static version of a generalized adaptive mesh pressure integration technique code, for progressive flooding of floating objects, is used to model the progression of the floodwater and the vessel's attitude. The probabilistic model suggested by the Marine Environment Protection Committee of the International Maritime Organization (MEPC-IMO) is considered for the collision induced probabilistic distribution of the damage boxes. A total of 90 damage cases are considered and comparisons of the maximum loads and the location where these take place is carried out relative to the intact case. The minimum design values for still water bending moment and shear force, included in the Common Structural Rules for Bulk Carriers and Tankers of the International Association of Classification Societies (IACS), are introduced in the analysis and their envelopes are compared with the numerically obtained values in light of a probabilistic assessment. Several conclusions are taken regarding the effects of the damage parameters variation, and important findings are presented specifically when accounting for the MEPC-IMO probabilistic distribution, in opposition to a uniform distribution of the damage cases. Highlights: Box-shaped damaged volumes are applied to an intact shuttle tanker in full load condition. For each configuration the vertical global loads are assessed at the final position of the ship. A quasi-static generalized adaptive mesh pressure integration technique is used for simulating progressive flooding. A total of 90 damage cases are considered and the maximum loads and their calculated. Conclusions are taken regarding the effects of the damage parameters' variation and of their distribution.